1982
DOI: 10.7326/0003-4819-96-6-858
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Shock Syndrome: Clinical, Laboratory, and Pathologic Findings in Nine Fatal Cases

Abstract: Clinical, laboratory, and pathologic findings in nine of the 12 patients who died from toxic shock syndrome in Minnesota are reported. All patients met the toxic shock syndrome case definition except for desquamation, which occurred in only one patient. Eight were menstruating and at least four were wearing tampons at the time of the acute illness. One patient was using napkins only. Noncardiogenic pulmonary edema was the only clinical development that could be used to predict a fatal outcome. Specific patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
5

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 15 publications
3
65
0
5
Order By: Relevance
“…The authors noted that pathological findings in toxic shock syndrome include lymphocytic infiltration of the myocardium and vacuolar cellular degeneration of myocardial cells. 9 They suggested that tumor necrosis factor (TNF) may have caused the reversible heart block seen in their patient since TNF impairs muscle electrical activity. 10 TNF also decreases myocardial contractility.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that pathological findings in toxic shock syndrome include lymphocytic infiltration of the myocardium and vacuolar cellular degeneration of myocardial cells. 9 They suggested that tumor necrosis factor (TNF) may have caused the reversible heart block seen in their patient since TNF impairs muscle electrical activity. 10 TNF also decreases myocardial contractility.…”
Section: Discussionmentioning
confidence: 99%
“…We (J. Q. Russell, unpublished observations) and others (2) have observed that Ag-activated T cells also traffic to the lung and kidneys, and we are examining the degree of tissue injury that results at these sites. This model might also serve to explain the liver dysfunction that is often observed after situations in which the immune system has been strongly activated largely outside the liver, such as by a superantigen in toxic shock syndrome (36,37). It also suggests that the normal number of resident liver lymphocytes in wild-type mice might induce tonic low levels of hepatocyte apoptosis in a Fas-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Grossly abnormal liver function values with hyperbilirubinemia, markedly elevated transaminase enzyme activity, and normal alkaline phosphate levels, as seen in my patient, have been reported only for two fatal cases studied by Larkin et al 2 Physicians should be aware of this complication of hepatic dysfunction in toxic shock syndrome, as early diagnosis, adequate fluid replacement, vasopressor therapy, and appropriate antistaphylococcal antibiotics can prevent fatal outcome. …”
Section: Staphylococcus Aureusmentioning
confidence: 99%